Case Report : Wanita 60 Tahun dengan Vertigo Perifer di Rumah Sakit Cut Meutia Aceh Utara - Meltri Rahma Desti; Herlina Sari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Vertigo is a phenomenon that is often encountered. Vertigo is a symptom or feeling where someone or objects around them seem to be moving or spinning, which is usually accompanied by nausea or loss of balance. . Cases of peripheral vertigo are more common with a percentage of 75% compared to cases of central vertigo. A 60 year old woman came to the emergency room at Cut Meutia Hospital with complaints of dizziness for 3 days before entering the hospital accompanied by nausea. The results of the romber test examination showed that the patient failed to maintain balance and the dix-hallpike showed lateral nystagmus +/+. Based on the history, physical examination and supporting examinations, the patient was diagnosed with peripheral vertigo ec Benign Paroxysmal Positional Vertigo (BPPV). Medical therapy was carried out in the form of Inf. Asering, Inj. Ondancetron/12h, Betahistine 6mg 3x1, Omeprazole 20mg 2x1 and Paracetamol 500mg 3x1.